Clusters formation and identification in the embryo stage on the example of the subsea technologies cluster in the North-Eastern England region - Siedlok, Franciszek; Andriani, Pierpaolo (Journal of Public Governance, 2007)
This paper examines the emergence of the subsea technologies cluster that followed the collapse of the previously dominating industries of shipbuilding and heavy engineering in the North East of England. By reconstructing the events that lead to emergence of the subsea technologies cluster, we decoupled and analyzed three main development trajectories. The case study is then interpreted using concepts rooted in complexity theory and co-evolutionary frameworks. In particular, we show that recombinant and nonadaptive (exaptational) processes constitute powerful theoretical frameworks to understand the social and technical dynamics related to the emergence of new clusters from the ashes of the collapsed ones. Based on the lessons learnt from the subsea case study, we draw some general conclusions for policies aimed to support embryonic clusters and propose a framework for the identification embryonic cluster in the context of industrial demise.